2014
DOI: 10.1121/1.4903917
|View full text |Cite
|
Sign up to set email alerts
|

Phoneme categorization relying solely on high-frequency energy

Abstract: Speech perception studies generally focus on the acoustic information present in the frequency regions below 6 kHz. Recent evidence suggests that there is perceptually relevant information in the higher frequencies, including information affecting speech intelligibility. This experiment examined whether listeners are able to accurately identify a subset of vowels and consonants in CV-context when only high-frequency (above 5 kHz) acoustic information is available (through high-pass filtering and masking of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…On the other hand MFCC #11 captures information in high frequency [9.5kHz -12.6kHz]. Recently researchers, supported by the advancements in equipment technology that captures a broader spectrum [47,48], have shown that there is perceptually relevant information on high frequency speech, affecting speech intelligibility. Both [47,49] concluded that high frequency speech characteristics are different in dysphonic versus control subjects, suggesting that the hoarseness characteristic of PD subjects, or in our case, the difference in hoarseness between "ON" and "OFF" states is what we are capturing with high coefficients of the MFCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand MFCC #11 captures information in high frequency [9.5kHz -12.6kHz]. Recently researchers, supported by the advancements in equipment technology that captures a broader spectrum [47,48], have shown that there is perceptually relevant information on high frequency speech, affecting speech intelligibility. Both [47,49] concluded that high frequency speech characteristics are different in dysphonic versus control subjects, suggesting that the hoarseness characteristic of PD subjects, or in our case, the difference in hoarseness between "ON" and "OFF" states is what we are capturing with high coefficients of the MFCC.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of these statistically-defined tone sequences on subsequent speech categorization suggests that listeners may keep a running estimate of the distributionally-defined LTAS across both speech and nonspeech sounds and encode subsequent sounds relative to, and contrastively with, these running averages [ 21 , 22 , 25 ]. Spectral contrast as a function of the LTAS may be an effective, domain-general process contributing to accommodation of talker differences across speech [ 21 24 , 26 , 29 33 ], including normalization of the sort described by Ladefoged and Broadbent [ 28 ], accommodation of individual differences in overall voice pitch that impact Mandarin lexical tone realization [ 24 ], the ability to adapt to a speaker’s style [casual vs. careful; 32 ] and the inability to adapt to some particular voice changes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related hearing loss, noise-induced hearing loss (NIHL), and ototoxicity may be observed as a highfrequency hearing loss that gradually progresses toward lower frequencies (Durrant et al, 2009;Seddon et al, 2012;Mehrparvar et al, 2014). The acoustic energy of extended high frequencies (EHFs) plays an important role in speech perception, especially in the presence of background noise (Rodríguez Valiente et al, 2014;Vitela et al, 2014;Vlaming et al, 2014). Despite this, the gradual change in hearing sensitivity may, initially, go unnoticed, as hearing perception is dominated by low-frequency hearing (Vlaming et al, 2014).…”
mentioning
confidence: 99%